A prayer for Owen Meany : a novel - Irving, John, 1942- (New York : Morrow, 1989)
In the summer of 1953, two 11-year-old boys--best friends--are playing in a Little League baseball game in New Hampshire. One of the boys hits a foul ball that kills his best friend's mother. Owen Meany believes he didn't hit the ball by accident. He believes he is God's instrument. What happens to Owen after 1953 is extraordinary and terrifying. He is Irving's most heartbreaking hero.
Also issued online.
Keywords: Vietnam War, 1961-1975 -- United States -- Fiction; Belief and doubt -- Fiction; Mothers -- Death -- Fiction; Male friendship -- Fiction; New Hampshire -- Fiction; Predestination -- Fiction; Birthfathers -- Fiction; Psychological fiction; Religious fiction